Keyless Coordinators<subtitle>The Family and Sexual Violence Coordination Scheme and its Challenges in Protecting Human Rights in Cases Involving Persons with Intellectual Disability</subtitle> - Linda Hoel; Karianne Moen (Nordic Journal of Studies in Policing)
From organisational perspectives, this study examines coordinatorsʼ experience in the field of domestic violence and sexual abuse, regarding the coordinator scheme and role. The paper has two related research questions: 1) In general, how do police organizational structures affect the coordinatorsʼ role and work? And 2) How does this reflect the coordinatorsʼ work to defend legal rights in cases involving persons with intellectual disability? The study is based on interviews with 11 coordinators. The analysis reveals that due to coordinatorsʼ organisational placement, they were not included in decision-making meetings, and that lack of mechanisms for accountability made the coordinatorsʼ work invisible. The concept of ʻkeyless coordinatorsʼ was developed to emphasise the need for mechanisms to ensure intra-organisational coordination of resources, competence, and shared understanding regarding the policeʼs work in this area, and in particular, to safeguard the legal rights of, and adapt the work to the needs of, persons with an intellectual disability.